2017
DOI: 10.1093/carcin/bgx009
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to DEHP metabolite, MEHP cause genotoxicity, mutagenesis and carcinogenicity in mammalian Chinese hamster ovary cells

Abstract: Di-(2-ethylhexyl) phthalate (DEHP), the common plasticizer used in the production of polyvinyl chloride, can be converted to the more potent metabolite mono-ethylhexyl phthalate (MEHP). Epidemiological studies have shown an association with elevated induction of rat hepatic cancer and reproductive toxicity in response to MEHP exposure. However, the mechanism of genotoxicity and carcinogenicity induced by MEHP treatment remains unclear. As a means to elucidate the mechanisms of action, lethality and mutagenicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…In alphabetical order we have included the following studies: Buñay et al 2017 [27], Chang et al 2017 [43].…”
Section: Revised Figure 1 Prisma Flow Diagrammentioning
confidence: 99%
“…In alphabetical order we have included the following studies: Buñay et al 2017 [27], Chang et al 2017 [43].…”
Section: Revised Figure 1 Prisma Flow Diagrammentioning
confidence: 99%
“…Phthalates are synthetic plasticizers, and they are widely used in the industrial products of medical devices, children's toys and clothing (Chang, Tseng, Lin, Chuang, & Chao, 2017; Du et al., 2016). Di‐(2‐ethylhexyl)phthalate is one of the most common subtypes of phthalates.…”
Section: Introductionmentioning
confidence: 99%
“…Human biomonitoring studies support the notion that exposure to phthalates impairs semen quality and decreases sex hormone levels causing fertility problems in reproductive-age men (Bloom et al, 2015;Liu et al, 2012;Wang et al, 2016. Several studies found statistically significantly lower sperm concentration and sperm counts when exposure to phthalates increased (Pant et al, 2008(Pant et al, , 2014Kranvogl et al, 2014;Specht et al, 2014;Bloom et al, 2015;Chang et al, 2017). Some others observed that sperm motility was statistically significantly lower when DEHP exposure increased (Pant et al, 2008;Huang et al, 2011;Jurewicz et al, 2013;Kranvogl et al, 2014;Axelsson et al, 2015).…”
Section: Endocrine Disrupting Properties and Related Disordersmentioning
confidence: 90%
“…Recently, Chang et al (2017) reported that also MEHP induces intracellular ROS production leading to DNA damage, with the amount of ROS generated being dependent on the MEHP concentration. Mammalian Chinese hamster ovary (AS52) cells were used in the Comet assay to evaluate whether MEHP causes DNA single-strand breaks at concentrations of 0, 10, 25 and 50 mM.…”
Section: Genotoxicity Of Phthalatesmentioning
confidence: 99%
See 1 more Smart Citation